An introduction to the Unitarian and Universalist traditions - Greenwood, Andrea, 1961-; Harris, Mark W. (Cambridge : Cambridge University Press, 2011)
"How is a free faith expressed, organised and governed? How are diverse spiritualities and theologies made compatible? What might a religion based in reason and democracy offer today's world? This book will help the reader to understand the contemporary liberal religion of Unitarian Universalism in a historical and global context. Andrea Greenwood and Mark W. Harris challenge the view that the Unitarianism of New England is indigenous and the point from which the religion spread. Relationships between Polish radicals and the English Dissenters existed and the English radicals profoundly influenced the Unitarianism of the nascent United States. Greenwood and Harris also explore the US identity as Unitarian Universalist since a 1961 merger and its current relationship to international congregations, particularly in the context of twentieth-century expansion into Asia"--
1. Introduction -- 2. Beginnings -- 3. Great Britain -- 4. From relevation to reason: America 1630-1833 -- 5. From reason to intuition to freedom: USA 1833-1894 -- 6. A religion for one world -- 7. Congregational polity -- 8. Worship -- 9. Sources of faith -- 10. Science and ecology -- 11. Architecture, art, and music -- 12. Education and social justice -- 13. Current issues, new directions.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 610, 650
Keywords: Unitarian Universalist Association; Unitarian churches -- History; Universalist churches -- History; Unitarian Universalist churches; RELIGION -- General; Unitarian churches; Unitarian Universalist churches; Universalist churches; Electronic books; History